مولانا بہاؤالدین بہائی اور ان کے افکار (Al-Qamar, 2023)
People with great imagination can born anywhere in the world. Mawlānā Bahā-ud- Bahā’ī Pitāfī is one such example. He was born in 1238 AH in Ghotki, district of Sindh. He got his education from Syed Ali Akbar Shah in a madarsa. He got married and had 6 children. He learned Arabic and Persian there and began teaching in the same institution. After that, he kept on teaching in far off places, but, ultimately, he settled in a village called Dad Laghari. He was one of the greatest sufi poets of his time. People often confuse him with Persian "Bahai baha ul din". But he is totally a different poet. It is his distinction that he is the first urdu poet of Ghotki. His poetry is full of peculiarities. He adores human beings in various ways and considers them the path to God.
Keywords: Sufi Poet; First Urdu Poet of Ghotki; Peculiarities Poetry; Mawlānā Bahā-ud- Bahā’ī Pitāfī